'And what language do you speak at home?' Ethnocentrism and cultural openness in teacher–parent interactions in disadvantaged and ethnically segregated schools. Issue 3 (3rd July 2019) - Payet, Jean-Paul; Deshayes, Fabien
ABSTRACT: This article, based on a deep ethnography in schools located in a disadvantaged multicultural context in Geneva (Switzerland), questions the way in which the local school system and teachers comprehend the cultural diversity of students and their parents. Oscillating between recognition and assimilation, teachers publicly adhere to discourses that emphasise cultural diversity, while limiting its expression, especially when a student encounters school difficulties. Teachers' meetings with parents are significantly influenced by the majority perspective, leaving the parents with little place to express their own needs. Nonetheless, within the conversation, some parents are able to assert practices that differ from those promoted by the host society. Ultimately, it seems that, in the absence of a multicultural position, teachers are limited to adopting hybrid practices that create unease and are evidence of limited understanding of multiculturality.